2008
DOI: 10.1091/mbc.e07-11-1124
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Hydroxylase PHD3 Activates Oxygen-dependent Protein Aggregation

Abstract: The HIF prolyl hydroxylases (PHDs/EGLNs) are central regulators of the molecular responses to oxygen availability. One isoform, PHD3, is expressed in response to hypoxia and causes apoptosis in oxygenated conditions in neural cells. Here we show that PHD3 forms subcellular aggregates in an oxygen-dependent manner. The aggregation of PHD3 was seen under normoxia and was strongly reduced under hypoxia or by the inactivation of the PHD3 hydroxylase activity. The PHD3 aggregates were dependent on microtubular inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 57 publications
(87 reference statements)
6
65
0
Order By: Relevance
“…We have previously described that exogenous PHD3 forms subcellular bodies in normoxic cells (Rantanen et al, 2008). To investigate the possible significance of PHD3 bodies in cancer the subcellular expression pattern of PHD3 was studied in clinical cancer samples using breast cancer and squamous cell carcinomas of head and neck region (HNSCC; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously described that exogenous PHD3 forms subcellular bodies in normoxic cells (Rantanen et al, 2008). To investigate the possible significance of PHD3 bodies in cancer the subcellular expression pattern of PHD3 was studied in clinical cancer samples using breast cancer and squamous cell carcinomas of head and neck region (HNSCC; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that under normoxia PHD3 aggregates in cytoplasmic/perinuclear speckles that contain chaperones and proteasomal components (Rantanen et al, 2008) and PHD3 can homomultimerize in complexes that might enhance its degradation by Siah2 E3 ubiquitin ligase (Nakayama et al, 2004;Nakayama et al, 2007). Noticeably, in some carcinoma cells the aggregation associates with enhanced apoptosis (Rantanen et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of note, functionally active PHD3 is particularly difficult to purify, even when expressed in eukaryotic cells (unpublished observations). This property of PHD3 might be related to its tendency to form protein aggregates [69,75]. In bacteria, coexpression of the bacterial chaperonins GroEL/ES substantially increased the yield of soluble PHD3 [18].…”
Section: Tricmentioning
confidence: 99%
“…NGF withdrawal causes PHD3 accumulation [104], and PHD3 enzymatic activity is required for the induction of KIF1B . Of note, it has been shown that EGFP-tagged exogenous PHD3 clusters around microtubule-like structures upon inhibition of the proteasome, suggesting that PHD3 might be transported by a microtubular motor protein [75]. Whether KIF1B is hydroxylated by PHD3 and how this induces the KIF1B protein remains to be determined.…”
Section: Kif1bmentioning
confidence: 99%